Development of Low Fat Goshtaba with Sodium Alginate - Jalal, Heena; Hussain, Syed Arshad; Bhat, M. Mansoor; Salahuddin, Mir; H, Asif (Journal of Meat Science, 2014)
A study was conducted with an objective to evaluate the effect of sodium alginate @ 0.1% (on weight basis) of batter on the quality of low fat Goshtaba. The raw emulsion was evaluated for physico-chemical parameters (pH, emulsion stability, proximate composition) while cooked product was evaluated for both physico-chemical and sensory parameters. All the physico-chemical parameters of raw emulsion except pH, protein and ash content showed significant (P<0.05) differences. However, in case of cooked product moisture, protein and fat content showed significant (P<0.05) differences. Similarly, in case of gravy, protein and fat (%) values showed significant (P<0.05) differences. Overall palatability scores were found significantly (P<0.05) better in low fat Goshtaba formulated with sodium alginate as compared to control samples. It was concluded that incorporation of sodium alginate improved quality and acceptance of low fat Goshtaba with 10% fat.